Struktura wydatków konsumpcyjnych gospodarstw domowych - Grzywińska-Rąpca, Małgorzata (The Structure of Consumption Expenditures of Households, 2005)
In the market economy system the directions of development of the market often depend on the behaviour by consumers. Expectations of consumers depend on numerous factors, including the economic ones. The level of income is the basic factor influencing the level of consumption. Consumers satisfy their needs while observing the rational hierarchy of those needs.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 317-320